1997
DOI: 10.2307/2275635
|View full text |Cite
|
Sign up to set email alerts
|

Non-constructive Galois-Tukey connections

Abstract: There are inequalities between cardinal characteristics of the continuum that are true in any model of ZFC, but without a Borel morphism proving the inequality. We answer some questions from Blass [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
2
Order By: Relevance
“…However it might be difficult. In [11] and [12], Mildenberger introduced another variation of reaping numbers r n and r n = r m (= r) holds for n, m ∈ ω but it is proved that there are no nice Galois-Tukey connections between Mildenberger's reaping numbers. .…”
Section: N-splitting Number and N-reaping Numbermentioning
confidence: 99%
“…However it might be difficult. In [11] and [12], Mildenberger introduced another variation of reaping numbers r n and r n = r m (= r) holds for n, m ∈ ω but it is proved that there are no nice Galois-Tukey connections between Mildenberger's reaping numbers. .…”
Section: N-splitting Number and N-reaping Numbermentioning
confidence: 99%
“…In [8], the first example of a correct inequality between the norms of two relations without a Borel morphism proving it was given. The older examples for non-existence of Borel morphisms are based upon incorrect inequalities and forcing, see [4] and Section 2 of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] we have shown that there are pairs of relations with no Borel morphism connecting them. The reason was a strong impact of the first of the two functions that constitute a morphism, the so-called function on the questions.…”
mentioning
confidence: 99%
See 2 more Smart Citations